Dual Laser-Aided UAV Motion Compensation for Vision-Based Displacement Measurement of High-Speed Railway Bridge - Thanh Chung, Truong; Quang Huy, Tran; Quoc My, Dang; Ngoc Hoa, Tran; Tien Thanh, Bui; De Roeck, Guido (Tạp chí Khoa học Công nghệ Giao Thông Vận Tải, 2025)
Unmanned Aerial Vehicles (UAVs) offer mobility and flexibility for vision-based structural health monitoring but are susceptible to motion-induced errors in displacement tracking. This study proposes a dual-laser compensation method in which two fixed laser beams, projected near the target to serve as reference points, are tracked to estimate UAV translation and rotation via affine transformation. By removing this motion component from the measured signal, the actual structural displacement can be obtained. Validation through both laboratory and field tests on a railway bridge demonstrates the effectiveness of the proposed method.